A preparation process for low-resistance polymer film using plastic sintered plate waste

By cleaning and processing the residual materials of plastic-fired plates, combining the mixing and stretching process of high-density polyethylene, ultra-high molecular weight polyethylene, nanosilver particles and carbon nanotubes, the energy consumption and pollution problems of filter material waste materials are solved, and the efficient production of low-resistance polymer films is achieved.

CN118927685BActive Publication Date: 2025-03-18SHANGHAI SUPERHIGH ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411428703.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-03-18
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing treatment methods for waste filter materials have problems of energy consumption and pollution, making it difficult to achieve efficient recycling, and it is difficult to produce low-resistance polymer films.

Method used

Through cleaning, crushing, grinding and melting methods, the residual material generated during the processing of the plastic-fired plate is converted into a low-resistance polymer film. The process includes steps such as mixing, stirring, sintering and three-stage stretching.

Benefits of technology

It realizes efficient recycling of plastic-burning board residual materials, and produces polymer films with low resistance and high strength, suitable for batteries, smart wearable devices and charging technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118927685B_ABST
    Figure CN118927685B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation process for making a low-resistance polymer film using waste plastic sintered plates, and belongs to the technical field of polymer film preparation. The present invention changes the conductive properties of the material by cleaning, crushing, grinding and melting the waste generated during the processing of the plastic sintered plates, and improves the efficient use of waste materials, thereby realizing the use of the waste generated at the head and tail of the plastic sintered plates to make a low-resistance polymer film; the present invention performs a three-stage stretching operation on the semi-finished film blank, and the polymer film after stretching is improved in terms of mechanical properties, electrical properties and thermal stability. By optimizing the stretching process, the waste of raw materials and the energy consumption in the processing process can be reduced, thereby reducing production costs. The stretching section operation can reduce defects and stress concentration inside the film material, and improve the overall quality and consistency of the finished product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer film preparation, and relates to a preparation process for making a low-resistance polymer film by utilizing plastic sintered plate waste. Background Art

[0002] The waste materials generated by existing filter materials are generally cleaned up daily with industrial waste and digested by solid waste units through incineration. This treatment method is relatively simple, but the disadvantages are obvious. On the basis of consuming energy, it also generates new dust and gas pollution, which is not conducive to green and low-carbon, and is not conducive to the recycling of resources.

[0003] Based on this, how to improve the recycling of waste filter materials, produce low-resistance polymer membranes, and make high-performance materials that turn waste into treasure serve various sectors of the national economy is an important topic that has received much attention from researchers in the filtration materials industry, and it is also a problem that needs to be urgently solved in today's materials field. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation process for making a low-resistance polymer film using plastic-sintered plate waste, which has the characteristics of low resistance and high strength.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A preparation process for making a low-resistance polymer film using waste plastic sintered board, using the waste generated during the processing of the plastic sintered board for recycling and upgrading. The waste consists of two parts: one is the fine granular material with burrs screened out during the processing of the plastic sintered board, and the other is the material cut off during product molding. The specific process of the preparation process of the low-resistance polymer film is as follows:

[0007] S1: weigh the raw materials, according to the mass percentage, the residual material is 78-82%, the high-density polyethylene is 15-20%, the nano silver particles are 1-2%, and the carbon nanotubes are 0.5-1%;

[0008] S2: pickling the carbon nanotubes with a hydrochloric acid solution having a mass fraction of 5%, washing them with deionized water after pickling, and draining them after washing;

[0009] S3: Mix the drained carbon nanotubes and high-density polyethylene in proportion, with a stirring rate of 550 r / min, a stirring temperature of 95° C., and a stirring time of 1 to 2 h to obtain a mixture A;

[0010] S4: adding the remaining material and nano silver particles in proportion, and then adding 2-3 wt% paraffin and 0.5-1 wt% catalyst, stirring at a speed of 950 r / min, a stirring temperature of 125° C., a stirring time of 1-2 h, and cooling to room temperature after the stirring is completed to obtain a mixture B;

[0011] S5: putting the mixture B into the mold, and performing the same frequency resonance treatment while putting the mixture B into the mold. After the treatment, sintering is performed at 235° C. for 2 hours, and air cooling is performed for 2 hours to obtain a semi-finished film blank;

[0012] S6: The stretching section of the semi-finished film blank is operated. The stretching section is divided into three sections. The first section is length stretching. The roller section temperature is 125°C and the stretching ratio is 1:6. The second section is correction stretching. The roller section is at ambient temperature and the stretching ratio is 1:1.2. The third section is the molding and finishing section, which performs longitudinal trimming and subsequent winding into a roll. After the stretching section operation, the low-resistance polymer film is obtained.

[0013] Furthermore, the component of the residual material is ultra-high molecular weight polyethylene with a molecular weight of 5 million.

[0014] Furthermore, the particle size of the residual material in S1 is ≤10 μm.

[0015] Furthermore, the particle size of the high-density polyethylene in the S1 is ≤15 μm.

[0016] Furthermore, the particle size of the nanosilver particles in S1 is ≤10 nm.

[0017] Furthermore, the particle size of the carbon nanotubes in S1 is ≤5 nm.

[0018] Furthermore, the catalyst in S4 is one of aluminum oxide, titanium dioxide and zinc oxide.

[0019] Furthermore, the cooling rate to room temperature in S4 is 3°C / min.

[0020] Furthermore, the parameters of the same frequency resonance in S5 are: a frequency of 500-1000 Hz, and a resonance treatment time of 5-10 minutes.

[0021] Furthermore, the wind cooling parameters in S5 are: wind speed of 1-2 m / s and wind pressure of 300-500 Pa.

[0022] The present invention changes the conductive properties of the waste materials generated during the processing of the plastic sintered plate through methods such as cleaning, crushing, grinding and melting, thereby improving the efficient utilization of the waste materials, thereby realizing the use of the waste materials generated at the head and tail of the plastic sintered plate to make a low-resistance polymer film, so that the recycled polymer film material can play a high cost-effective role in battery production, a new generation of smart wearable equipment and charging technology materials, providing more options and solving the problems existing in traditional technologies.

[0023] The invention completes the recycling of the waste plastic sintered board by washing, crushing, grinding, screening, secondary grinding and re-screening the waste, thereby improving the efficient utilization of waste materials. In the invention, the crusher used is: Jinma 600 type, and the grinding machine used is: BWCJ1000.

[0024] Ultra-high molecular weight polyethylene has extremely high wear resistance, and its impact strength ranks among the best among all plastics. The impact strength increases with the increase of molecular weight. Ultra-high molecular weight polyethylene has a small friction coefficient, good fluidity, excellent self-lubricating properties, and shows good stability to most chemicals and solvents.

[0025] High-density polyethylene has high tensile strength and yield strength, and can maintain stable performance at high temperatures. High-density polyethylene is also a good electrical insulating material and can be easily processed into various products through extrusion, injection molding and other processes.

[0026] Nanosilver particles have extremely high conductivity and can significantly reduce the resistivity of polymer films. Nanosilver also has broad-spectrum antibacterial properties, which helps to improve the hygienic properties of polymer films. Nanosilver particles can be stably dispersed in the polymer matrix and are not easy to agglomerate.

[0027] Carbon nanotubes can significantly improve the mechanical properties of polymer films, and help further improve the conductivity and heat dissipation performance of polymer films. Carbon nanotubes can maintain stable performance in a variety of chemical environments.

[0028] The invention significantly reduces the resistivity of the polymer film and improves its conductive performance by adding nano silver particles. The combination of high-density polyethylene and ultra-high molecular weight polyethylene and the addition of carbon nanotubes significantly enhance the mechanical strength, toughness and wear resistance of the polymer film. During the high-temperature sintering process, the polymer film can maintain stable performance and is not easy to deform or degrade. Through a sophisticated preparation process including stirring, mixing, sintering and stretching steps, the polymer film is easy to be processed into various shapes and sizes. The catalysts and additives used in the preparation process meet environmental protection requirements and are pollution-free to the environment.

[0029] The invention adds paraffin wax as a lubricant, which can reduce the friction of the raw materials during the mixing and processing process, making the stirring and mixing process smoother. The addition of paraffin wax can improve the fluidity of the composite material, making it easier to be processed into a desired shape and size through processes such as extrusion and injection molding; at the same time, the paraffin wax can also improve the demoulding property of the composite material, reduce the residue and adhesion in the mold, and in the stretching section operation, the melting of the paraffin wax can provide a certain lubrication and shaping effect, which helps the polymer film to maintain a uniform thickness and shape during the stretching process, and reduces the stress concentration and cracking phenomenon during the stretching process.

[0030] By adding 0.5~1wt% of catalyst, the interaction and fusion between raw materials such as high-density polyethylene, ultra-high molecular weight polyethylene, nanosilver particles and carbon nanotubes can be accelerated, thereby shortening the mixing time and improving production efficiency. The addition of catalyst can promote the interaction and compatibility between different components, allowing them to be more evenly dispersed in the matrix to form a stable blending system.

[0031] Through the same-frequency resonance treatment, the materials in the mold and the materials and the mold can support each other and become one, so that the density of the materials in the mold is sufficient and the filling is full, which helps the semi-finished product to stretch evenly during the later stretching and film forming.

[0032] Through stretching treatment, the polymer chains can be rearranged in a specific direction to form a more ordered structure, thereby improving the physical and electrical properties of the material; stretching can enhance the strength and toughness of the film, making it more resistant to external mechanical stress and impact; during the stretching process, the distribution and arrangement of conductive fillers such as nanosilver particles and carbon nanotubes in the film will change, thereby optimizing the resistivity of the film and achieving the desired low resistance effect; through three-stage stretching, the length, width and thickness of the film can be controlled separately to achieve precise molding and cutting to meet the needs of different application scenarios.

[0033] Beneficial effects of the present invention:

[0034] The present invention changes the conductive properties of the waste materials generated during the processing of the plastic-sintered plate by cleaning, crushing, grinding and melting, thereby improving the efficient use of waste materials, so as to realize the use of the waste materials generated at the head and tail of the plastic-sintered plate to make a low-resistance polymer film. Through the combined use of the above processes, the comprehensive utilization of the waste materials and waste materials in the processing of the plastic-sintered filter plate is realized, the application properties and conductive properties of the materials are changed, the efficient recycling of waste materials is improved, and the polymer film produced by the process has low resistance;

[0035] The present invention performs a three-stage stretching operation on the semi-finished film blank. The polymer film after stretching is improved in terms of mechanical properties, electrical properties and thermal stability. The three-stage stretching process can be produced continuously and stably, thereby improving production efficiency. By optimizing the stretching process, the waste of raw materials and energy consumption in the processing process can be reduced, thereby reducing production costs. The stretching operation can reduce defects and stress concentration inside the film material, thereby improving the overall quality and consistency of the finished product. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0037] Figure 1 A process roadmap for recycling model of plastic fired board waste;

[0038] Figure 2 A process route for producing low-resistance polymer films from plastic-sintered board waste. DETAILED DESCRIPTION

[0039] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.

[0040] Example 1

[0041] S1: weigh the raw materials, according to the mass percentage, the residual material is 80%, the high-density polyethylene is 18%, the nano silver particles are 1.5%, and the carbon nanotubes are 0.5%;

[0042] The components of the residual material are ultra-high molecular weight polyethylene with a molecular weight of 5 million, a particle size of ≤10 μm, a particle size of high-density polyethylene of ≤15 μm, a particle size of nano silver particles of ≤10 nm, and a particle size of carbon nanotubes of ≤5 nm;

[0043] S2: pickling the carbon nanotubes with a hydrochloric acid solution having a mass fraction of 5%, washing them with deionized water after pickling, and draining them after washing;

[0044] S3: mixing the drained carbon nanotubes and high-density polyethylene in proportion, stirring at a rate of 550 r / min, a temperature of 95° C., and a stirring time of 1 h to obtain a mixture A;

[0045] S4: adding the remaining material and nano silver particles in proportion, and then adding 3wt% paraffin wax and 1wt% alumina, stirring at a speed of 950r / min, a stirring temperature of 125°C, a stirring time of 2h, cooling to room temperature after stirring, and a cooling rate to room temperature of 3°C / min to obtain a mixture B;

[0046] S5: putting the mixture B into the mold, and performing the same frequency resonance treatment while putting the mixture B into the mold. The parameters of the same frequency resonance are: the frequency is 800 Hz, the resonance treatment time is 7 minutes, and after the treatment is completed, sintering is performed at 235° C. The sintering time is 2 hours, and the wind cooling is 2 hours. The wind speed is 1.5 m / s and the wind pressure is 400 Pa to obtain a semi-finished film blank;

[0047] S6: The stretching section of the semi-finished film blank is operated. The stretching section is divided into three sections. The first section is length stretching. The roller section temperature is 125°C and the stretching ratio is 1:6. The second section is correction stretching. The roller section is at ambient temperature and the stretching ratio is 1:1.2. The third section is the molding and finishing section, which performs longitudinal trimming and subsequent winding into a roll. After the stretching section operation, the low-resistance polymer film is obtained.

[0048] Example 2

[0049] S1: weigh the raw materials, according to the mass percentage, the residual material is 78%, the high-density polyethylene is 20%, the nano silver particles are 1%, and the carbon nanotubes are 1%;

[0050] The components of the residual material are ultra-high molecular weight polyethylene with a molecular weight of 5 million, a particle size of ≤10 μm, a particle size of high-density polyethylene of ≤15 μm, a particle size of nano silver particles of ≤10 nm, and a particle size of carbon nanotubes of ≤5 nm;

[0051] S2: pickling the carbon nanotubes with a hydrochloric acid solution having a mass fraction of 5%, washing them with deionized water after pickling, and draining them after washing;

[0052] S3: Mixing the drained carbon nanotubes and high-density polyethylene in proportion, stirring at a rate of 550 r / min, a temperature of 95° C., and a stirring time of 2 h to obtain a mixture A;

[0053] S4: adding the remaining material and nano silver particles in proportion, and then adding 2wt% paraffin and 0.5wt% titanium dioxide, stirring at a speed of 950r / min, a stirring temperature of 125°C, a stirring time of 2h, cooling to room temperature after stirring, and a cooling rate to room temperature of 3°C / min to obtain a mixture B;

[0054] S5: putting the mixture B into the mold, and performing the same-frequency resonance treatment while putting the mixture B into the mold. The parameters of the same-frequency resonance are: the frequency is 500 Hz, the resonance treatment time is 10 minutes, and after the treatment is completed, sintering is performed at 235° C. The sintering time is 2 hours, and the wind cooling is 2 hours. The wind speed is 1 m / s and the wind pressure is 300 Pa to obtain a semi-finished film blank;

[0055] S6: The stretching section of the semi-finished film blank is operated. The stretching section is divided into three sections. The first section is length stretching. The roller section temperature is 125°C and the stretching ratio is 1:6. The second section is correction stretching. The roller section is at ambient temperature and the stretching ratio is 1:1.2. The third section is the molding and finishing section, which performs longitudinal trimming and subsequent winding into a roll. After the stretching section operation, the low-resistance polymer film is obtained.

[0056] Example 3

[0057] S1: weigh the raw materials, according to the mass percentage, the residual material is 82%, the high-density polyethylene is 16%, the nano silver particles are 1%, and the carbon nanotubes are 1%;

[0058] The components of the residual material are ultra-high molecular weight polyethylene with a molecular weight of 5 million, a particle size of ≤10 μm, a particle size of high-density polyethylene of ≤15 μm, a particle size of nano silver particles of ≤10 nm, and a particle size of carbon nanotubes of ≤5 nm;

[0059] S2: pickling the carbon nanotubes with a hydrochloric acid solution having a mass fraction of 5%, washing them with deionized water after pickling, and draining them after washing;

[0060] S3: Mixing the drained carbon nanotubes and high-density polyethylene in proportion, stirring at a rate of 550 r / min, a temperature of 95° C., and a stirring time of 2 h to obtain a mixture A;

[0061] S4: adding the remaining material and nano silver particles in proportion, and then adding 3wt% paraffin and 1wt% zinc oxide, stirring at a speed of 950r / min, a stirring temperature of 125°C, a stirring time of 1h, and cooling to room temperature after stirring at a cooling rate of 3°C / min to obtain a mixture B;

[0062] S5: putting the mixture B into the mold, and performing the same frequency resonance treatment while putting the mixture B into the mold. The parameters of the same frequency resonance are: the frequency is 1000 Hz, the resonance treatment time is 5 minutes, and after the treatment is completed, sintering is performed at 235° C. The sintering time is 2 hours, and the wind cooling is 2 hours. The wind speed is 2 m / s and the wind pressure is 500 Pa to obtain a semi-finished film blank;

[0063] S6: The stretching section of the semi-finished film blank is operated. The stretching section is divided into three sections. The first section is length stretching. The roller section temperature is 125°C and the stretching ratio is 1:6. The second section is correction stretching. The roller section is at ambient temperature and the stretching ratio is 1:1.2. The third section is the molding and finishing section, which performs longitudinal trimming and subsequent winding into a roll. After the stretching section operation, the low-resistance polymer film is obtained.

[0064] Comparative Example 1

[0065] In this comparative example, no nanosilver particles were added during the preparation process, and the remaining steps were consistent with those in Example 1.

[0066] Comparative Example 2

[0067] In this comparative example, paraffin was not added during the preparation process, and the remaining steps were consistent with those in Example 1.

[0068] Comparative Example 3

[0069] In this comparative example, no catalyst was added during the preparation process, and the remaining steps were consistent with those in Example 1.

[0070] Comparative Example 4

[0071] This comparative example does not perform the same frequency resonance treatment during the preparation process, and the remaining steps are consistent with Example 1.

[0072] Comparative Example 5

[0073] This comparative example does not carry out the second and third stretching stage operations, and the remaining steps are consistent with Example 1.

[0074] The resistance test of the film of the embodiment and the comparative example was carried out using a Teichman TM385 digital surface resistance tester; the tensile properties of the film were tested according to the standard of GB / T 1040-2006;

[0075] The experimental data are summarized in the following table:

[0076]

[0077] Experimental data show that the addition of paraffin and catalyst effectively improves the strength of the polymer film, while the addition of nanosilver particles and the three-stage stretching operation effectively reduce the resistance of the polymer film surface.

[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for preparing a low-resistance polymer film using plastic sintered plate waste, characterized in that: The waste materials generated during the processing of the plastic sintered board are recycled and upgraded. The waste materials are divided into two parts: one is the fine granular material with burrs screened out during the processing of the plastic sintered board, and the other is the material cut off during the product molding. The specific process of the preparation process of the low-resistance polymer film is as follows: S1: weigh the raw materials, according to the mass percentage, the residual material is 78-82%, the high-density polyethylene is 15-20%, the nano silver particles are 1-2%, and the carbon nanotubes are 0.5-1%; S2: pickling the carbon nanotubes with a hydrochloric acid solution having a mass fraction of 5%, washing them with deionized water after pickling, and draining them after washing; S3: Mix the drained carbon nanotubes and high-density polyethylene in proportion, with a stirring rate of 550 r / min, a stirring temperature of 95° C., and a stirring time of 1 to 2 h to obtain a mixture A; S4: adding the remaining material and nano silver particles in proportion, and then adding 2-3 wt% paraffin and 0.5-1 wt% catalyst, stirring at a speed of 950 r / min, a stirring temperature of 125° C., a stirring time of 1-2 h, and cooling to room temperature after the stirring is completed to obtain a mixture B; S5: putting the mixture B into the mold, and performing the same frequency resonance treatment while putting the mixture B into the mold. After the treatment, sintering is performed at 235° C. for 2 hours, and air cooling is performed for 2 hours to obtain a semi-finished film blank; S6: The stretching section of the semi-finished film blank is operated. The stretching section is divided into three sections. The first section is length stretching. The roller section temperature is 125°C and the stretching ratio is 1:

6. The second section is correction stretching. The roller section is at ambient temperature and the stretching ratio is 1:1.

2. The third section is the molding and finishing section, which performs longitudinal trimming and subsequent winding into a roll. After the stretching section operation, the low-resistance polymer film is obtained.

2. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The component of the residual material is ultra-high molecular weight polyethylene with a molecular weight of 5 million.

3. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The particle size of the residual material in S1 is ≤10 μm.

4. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The particle size of the high-density polyethylene in the S1 is ≤15 μm.

5. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The particle size of the nanosilver particles in S1 is ≤10 nm.

6. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The particle size of the carbon nanotubes in S1 is ≤5 nm.

7. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The catalyst in S4 is one of aluminum oxide, titanium dioxide and zinc oxide.

8. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The cooling rate to room temperature in S4 is 3°C / min.

9. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The parameters of the same frequency resonance in S5 are: a frequency of 500-1000 Hz, and a resonance treatment time of 5-10 minutes.

10. The process for preparing a low-resistance polymer film using plastic-sintered board waste according to claim 1, characterized in that: The wind cooling parameters of S5 are: wind speed of 1~2m / s and wind pressure of 300~500Pa.

Citation Information

Patent Citations

  • Preparation method of ultrahigh molecular weight polyethylene flat membrane

    CN102744885A

  • Ultrahigh molecular weight polyethylene composite material and preparation method thereof

    CN110564035A